Jihad ekonomi Islam - Jafril Khalil (Depok : Gramata Pub., 2010)
Islamic economic system and its role in poverty alleviation in Indonesia.
Includes bibliographical references (p. 311-315).
Keywords: Economics -- Religious aspects -- Islam; Islam -- Economic aspects -- Indonesia; Poverty -- Indonesia